2017
DOI: 10.1080/14767058.2017.1366984
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic biomarkers for diagnostic of early-onset neonatal sepsis

Abstract: Accurate identification of early onset neonatal sepsis (EOS) is challenging. Blood culture has been considered as a gold standard method but the identification of EOS is intricate by a high false-negative results. This review provides an overview of biomarkers as indicators for the diagnosis of EOS. There is an affluence of studies appraising diagnostic indicators in the identification of EOS. Acute-phase reactants, cytokines, and cell surface antigens have been investigated as indicators for EOS, but none of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 108 publications
0
42
0
7
Order By: Relevance
“…In a recent review on biomarkers in sepsis, the authors concluded that biomarkers like PCT, IL-6, and IL-8 can be the key to personalized targeted treatment in the future clinical management of sepsis. 33 Memar et al 34 proposed that IL-6 is the most potent marker for evaluation of EONS prognosis, whereas PCT and CRP seem to be appropriate indicators for the detection and monitoring of antibiotics therapy. In their meta-analyses and systematic review, they concluded that a panel of sepsis biomarkers along with present routine tests can make early identification easier, and appropriate management and improved outcome may be more efficient than with a single indicator.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review on biomarkers in sepsis, the authors concluded that biomarkers like PCT, IL-6, and IL-8 can be the key to personalized targeted treatment in the future clinical management of sepsis. 33 Memar et al 34 proposed that IL-6 is the most potent marker for evaluation of EONS prognosis, whereas PCT and CRP seem to be appropriate indicators for the detection and monitoring of antibiotics therapy. In their meta-analyses and systematic review, they concluded that a panel of sepsis biomarkers along with present routine tests can make early identification easier, and appropriate management and improved outcome may be more efficient than with a single indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of pCRP into pro-inflammatory mCRP might directly link CRP to inflammation. CRP is considered as a serum biomarker in patients undergoing acute inflammatory response ( 2 4 ). The elevation in baseline CRP level was shown to be useful to gauge chronic inflammation and tissue damage resulting from excessive inflammation or failure of the initial inflammatory response ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has improved sensitivity when compared to CRP, and may allow reduced antibiotic duration in neonates > 34 weeks with suspicion for EOS [ 29 ]. Unfortunately, procalcitonin, along with other immunologic mediators such as IL-6, are often not readily available in the clinical setting [ 30 ]. While frequently obtained, the lack of reliability of more common laboratory values is reflected in their non-significance as key drivers of antibiotic duration in our study.…”
Section: Discussionmentioning
confidence: 99%